Constructing adverse outcome pathway for per- and polyfluoroalkyl substances and retinoblastoma based on PI3K-AKT/MAPK signaling pathway - Yuyan GUI; Tingji WANG; Minghao WANG; Yaqi XU; Yunhui ZHANG (环境与职业医学)
BackgroundExposure to per- and polyfluoroalkyl substances (PFAS) is associated with various cancers, and recent studies suggest it may also increase the risk of retinoblastoma (RB) in newborns. However, the pathogenic mechanisms remain unclear. ObjectiveBy constructing an adverse outcome pathway (AOP) framework based on public databases to elucidate the potential mechanisms linking PFAS and RB. MethodsChemical-gene interactions and disease-gene interactions from the Comparative Toxicogenomics Database were retracted to identify key toxicological disruption pathways using Kyoto Encyclopedia of Genes and Genomes (KEGG) and a priori knowledge. The Pathview package in R was employed to predict molecular initiating events, key events, and their associated phenotypes, for further understanding the relevant gene-molecule interaction toxicity pathway network. Molecular docking techniques were utilized to validate the affinity of PFAS for these molecular initiating events. An AOP framework focused on toxicological pathways was developed using classical AOP methodologies. ResultsThe PI3K-AKT/MAPK signaling pathway was identified as a potential toxicological pathway involved in PFAS-related RB development, based on KEGG and a priori knowledge. The activation of receptor tyrosine kinases (RTKs) served as the molecular initiating event, leading to the activation of key oncogenes such as RAS and AKT, as well as nuclear factor kappa-light chainenhancer of activated B cells (NF-κB), along with the inhibition of the tumor suppressor gene P53. In this study, 14 types of PFAS demonstrated good binding affinity with most RTKs, with chlorinated polyfluorinated ether sulfonates (Cl-PFESAs) showing particularly favorable predicted binding. Oncogenes, including the c-kit-encoded tyrosine kinase receptor for stem cell factor, epidermal growth factor receptor, and neurotrophic tyrosine kinase receptor 1, were identified as the receptors with the best predicted binding affinity. ConclusionThe PI3K-AKT/MAPK signaling pathway may serve as a potential toxicological mechanism linking PFAS to an increased risk of RB.